A Study on the Current Israeli Social and Political Movements: What Role for Women? - Daniele, G. (4th European Conference on Politics and Gender (ECPG), 2015)
This paper proposal is principally founded on the theoretical analysis and the fieldwork evaluation reported on in my Ph.D. dissertation, which has just been published by Routledge in the form of a book entitled Women, Reconciliation and the Israeli-Palestinian Conflict: The Road Not Yet Taken. This work involved a critical investigation of the interconnection existing between women’s political activism and paradigms of recognition and reconciliation in Palestine/Israel, with a specific focus on feminist theorizations of gender constructions and peace building. Throughout the paper I submit for your consideration I intend to expand on my previous work by looking at the heterogeneities (mostly related to ethnic, national, gender and class differences) existing within Israeli grassroots activism, and in particular by tackling the predominant narrative that addresses such a context in terms of a single and homogeneous platform. In documenting their internal relationships, tensions and challenges I aim at discussing the role played by women involved in the Israeli peace movement and in other types of socio-political activism, such as those rising to prominence in Summer 2014 during the Israeli Operation Protective Edge as well as those characterising what has been defined as the ‘Tent Protest’ in Summer 2011, which have gone through divisions of ethnicity, nationality, gender and class. Taking into consideration asymmetries of power and privileges among the different components and the backgrounds of the protagonists, I examine the foremost examples of such movements that have sprung up in Israel in recent times and in which women have been prominent partners. In detail, I plan to explore alternative political strategies from women activists belonging to minority communities, with a view to overcoming the one-dimensional agenda promoted mostly by leading Ashkenazi middle class groups.